Evaluasi Akurasi dan Presisi Alat Hematology Analyzer Mindray BC-5380 Mode Predilute Terhadap Kadar Hemoglobin pada Darah Kapiler - Dwi Apriliani; Yayuk Mundriyastutik; Arief Adi Saputro (Poltekkes Kemenkes Semarang, 2025)
Technological advances affect the automation of laboratory equipment, one of which is haemoglobin examination with a haematology analyzer that has several modes of examination to improve accuracy and precision. The haemoglobin test data at RSU Fastabiq Sehat PKU Muhammadiyah Pati reached 25,365 tests. Predilute mode on the Mindray BC-5380 haematology analyser is rarely used, only about 2%, very much different from the use of Whole Blood (WB) mode which reaches a percentage of 98%. This study aims to evaluate the accuracy and precision of the Hematology Analyzer Mindray BC-5380 in Predilute mode for measuring haemoglobin levels using capillary blood at RSU Fastabiq Sehat PKU Muhammadiyah Pati. The methodology used in this study was descriptive quantitative with a cross-sectional approach. Data was obtained through measurement of haemoglobin using the device, which was then analysed to assess accuracy and precision. The results showed a bias value of 2.58%, indicating good accuracy. The coefficient of variation (CV) value of 5.52% exceeded the limit set by the manufacturer, indicating poor precision. Further evaluation using the Levey-Jenning graph and Westgard's rule indicated a 12s deviation on the fifth day, indicating the possibility of systematic or random errors. The Mindray BC-5380 predilute mode haematology analyser had good accuracy of haemoglobin levels in capillary blood, but poor precision compared to the manufacturer's values.